2022
DOI: 10.1055/a-1854-2352
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Management of Microtia

Abstract: Microtia techniques have evolved to improve aesthetic outcomes, reduce donor site morbidities, and reduce complications. Patients with microtia commonly have aural atresia associated with conductive hearing loss. We present the evolution of our technique for microtia reconstruction and considerations for hearing management in these patients. Keywords: Microtia, aural atresia, autologous rib reconstruction, contemporary management

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Clinically, 63.8% of patients presented with grade III microtia, predominantly affecting the right side (57.0%), in line with global trends (Abrol et al, 2022; Andrews & Hohman, 2023; Luquetti et al, 2012; van Nunen et al, 2014; Widodo et al, 2021; Wu et al, 2010). Given the high incidence of grade III microtia, a corresponding prevalence of hearing loss was expected.…”
Section: Discussionsupporting
confidence: 61%
“…Clinically, 63.8% of patients presented with grade III microtia, predominantly affecting the right side (57.0%), in line with global trends (Abrol et al, 2022; Andrews & Hohman, 2023; Luquetti et al, 2012; van Nunen et al, 2014; Widodo et al, 2021; Wu et al, 2010). Given the high incidence of grade III microtia, a corresponding prevalence of hearing loss was expected.…”
Section: Discussionsupporting
confidence: 61%
“…13,14,16 Autologous costochondral microtia reconstruction has been the favored surgical approach for many years which may be complemented by an earlier atresiaplasty if the child is an appropriate surgical candidate. [17][18][19] Adhesive-retained auricular prosthesis alternatively offer a nonsurgical option for select patients. 17,20 These reparative operations can come with financial and personal health costs to patients and their families that are exacerbated by significant disparities across a number of patient-level and hospital-level factors.…”
mentioning
confidence: 99%
“…[17][18][19] Adhesive-retained auricular prosthesis alternatively offer a nonsurgical option for select patients. 17,20 These reparative operations can come with financial and personal health costs to patients and their families that are exacerbated by significant disparities across a number of patient-level and hospital-level factors. Specific minority groups and patients from low-resource settings may be particularly impacted as previous studies have demonstrated a greater incidence of microtia in these patient populations.…”
mentioning
confidence: 99%
See 2 more Smart Citations